Factors Influencing Tourists' Purchase Behavior of Local Dry Fruits in Skardu, Gilgit-Baltistan: https://doi.org/10.55966/assaj.2025.4.1.087 - Dostdar Hussain; Muhammad Hassnain; Dr. Ibrahim Hussain; Mehjabeen Alam; Muhammad Hadi (`, 2025)
The study explores the key determinants of tourists' buying behavior for Local Dry Fruits in Skardu, a very prominent and scenic tourist destination in Gilgit-Baltistan, Pakistan. It is also famous for its local dry fruits, which are an essential part of its traditional identity and also play a very vital role in the regional economy. The study uses a structured questionnaire with 350 tourists drawn from a convenience sampling to examine the influence of cultural, social, psychological, and economic factors on tourists' purchase intentions. The relationship and magnitude of contributing factors were compared with descriptive and inferential statistics. From the results, it can be seen that all of the variables have a positive relationship with purchase intention, with psychological and economic factors having the greatest effect. Local businesses may find opportunities in realizing that by matching tourists’ expectations, in their marketing and product strategies, they can increase sales and customer confidence, and lead to sustainable tourism development in the area. Keywords: Buying Intention, Tourist, Culture, Social, Psychological, Economic JEL Classification: M3; Q13; R11; L83